Range expansion for pico cell in heterogeneous LTE - A cellular networks - Yasir, Basim A.; Su, Gang; Bachache, Nasseer (2012 2nd International Conference on Computer Science and Network Technology, 2012)
In LTE-Advanced, a heterogeneous network (HetNet) where femtocells and picocells overlaid onto macrocells is extensively discussed in addition to traditional well-planned macrocell deployment to improve further the system throughput. recently, the Pico cell range expansion (CRE) in the Heterogeneous Cellular Networks has received a great attention. Thus, Pico cells are added to a macro-cell layout aiming for benefiting average system throughput from cell-splitting. Considering that the large coverage of macro cell can limit the cell-splitting gains, cell range expansion (CRE) is employed to increase the fraction of UEs camped on pico cells. However, some pico user equipments (UEs) suffer from macro cells due to cell range extension. In this paper, we proposed the path loss from macro eNodeB (MeNB) using large downlink reference signals received power (DL-RSRP), with various bias values to increase coverage and capacity for the Pico cell, to associate much user equipment for Pico base station. In our experiments, show that the proposed scheme can remarkably improve cell edge spectral efficiency as well as overall system capacity.